A city-scale IoT architecture for monumental structures monitoring. (January 2019) - Addabbo, Tommaso; Fort, Ada; Mugnaini, Marco; Panzardi, Enza; Pozzebon, Alessandro; Vignoli, Valerio
Highlights: The presented displacement sensor achieves a 10 μn precision. The sensor node has an ideal life time of 794 days. A more complex multi-layer cluster-tree network topology is presented. The deployed LoRa network infrastructure proved to cover the whole city centre. The sensor measures the expansion and contraction processes of the wall structure. Abstract: In this paper the authors describe the architecture of an IoT infrastructure to be used for the monitoring of large scale monumental structures. The proposed monitoring network is composed by very low power sensor nodes, provided with LoRa connectivity, able to measure displacements of structural cracks in buildings with a ten-micrometer degree of resolution. Description is provided about the functioning of the Displacement Sensor, the structure of the Sensor Node and the overall Network architecture. Moreover, test results are discussed about the data collection and network coverage for the medieval City Walls in the city of Siena, where two sensor nodes were installed and acquired data for about one year. Nevertheless, the proposed architecture can be applied to any context where a City-Scale monitoring is required.